A política urbana e a Extrafiscalidade como estímulo à proteção dos conjuntos urbanos tombados no Brasil - Vieira, Bruno Soeiro (2016)
The right to the urban environment, as a fundamental right of the human being, must be protected by the state and by society in a joint and harmonious action. In the cities environment, the theme of the built cultural heritage that compose the scenario of Brazilian historical cities requires attention. These isolated buildings and urban settlements more clearly represent urban identity and memory and their study makes it possible to understand how the spatial configuration process of cities, their historical evolution, the actors that constructed it and the socioeconomic context which buildings were built. Therefore, it is understood that the protection of built cultural real estate located in Brazilian cities must be carried out through all legal instruments in force in the Brazilian urban planning order. However, it is understood that the legal instrument of historical-cultural preservation, although important, is insufficient to effectively protect the built cultural patrimony, which is so important to the preservation of the memory and identity of Brazilian cities. Thus, it is necessary that alternative instruments are also used in order to improve the protection of the urban environment in the artificial and cultural aspects. From this evidence, this academic thesis decided to investigate the use of municipal taxes in the extra-fiscal perspective with the purpose of stimulating the preservation, conservation and restoration of the set of cultural properties built of significant historical and cultural value located in the historical cities scattered throughout the country in which there are Urban groups listed by the National Historical and Artistic Heritage Institute (IPHAN)